PERAN INTRAPRENEURSHIP DALAM MENCIPTAKAN KEUNGGULAN BERSAING PERUSAHAAN - Mulyanto, Kukuh (STIE Totalwin Semarang, 2013)
Intrapreneurship has been acknowledged in literature and practice as a vital element of economic and organizational growth, success and competitiveness and can be considered as a unique competitive advantage. The purpose of the paper is to provide a comprehensive analysis of the concept of intrapreneurship. Concluding, the paper suggests directions for future research.